Unraveling the interconversion pharmacokinetics and oral bioavailability of the major ginger constituents: [6]-gingerol, [6]-shogaol, and zingerone after single-dose administration in rats - Songvut, Phanit; Nakareangrit, Watanyoo; Cholpraipimolrat, Wanida; Kwangjai, Jackapun; Worasuttayangkurn, Luksamee; Watcharasit, Piyajit; Satayavivad, Jutamaad (Frontiers in Pharmacology, 2024)
Background: The available in vitro evidences suggest the inherent instability and interconvertibility of [6]-gingerol and [6]-shogaol. However, limited data on their in vivo interconversion hinder understanding of their influence on the pharmacokinetic profiles. Purpose: This study presents the first comprehensive in vivo investigation aiming to determine the interconversion pharmacokinetics in rats, and elucidate the oral bioavailability, target distribution, biotransformation, and excretion profiles of the key ginger constituents, [6]-gingerol, [6]-shogaol, and zingerone. Methods: The pharmacokinetics was investigated through single intravenous (3 mg/kg) or oral (30 mg/kg) administration of [6]-gingerol, [6]-shogaol, or zingerone, followed by the determination of their tissue distribution after oral dosing (30 mg/kg). Intravenous pharmacokinetics was leveraged to evaluate the interconversion, circumventing potential confounders associated with the oral route. Results: All rats tolerated these compounds throughout the pharmacokinetic study. The parent compounds exhibited rapid but partial absorption, and extensive organ distribution with substantial biotransformation, thereby limiting the oral bioavailability of each compound to below 2% when administered as pure compounds. Conversion of [6]-gingerol to [6]-shogaol after intravenous administration, demonstrated a significantly larger clearance compared to the reverse conversion ([6]-shogaol to [6]-gingerol). The irreversible metabolic clearance for both compounds was significantly greater than their reversible bioconversions. Furthermore, [6]-gingerol underwent biotransformation to zingerone. Conjugated glucuronides were eliminated partly through renal excretion, with minimal fecal excretion. Conclusion: This in vivo investigation demonstrates the influence of interconversion on the disposition kinetics of [6]-gingerol, [6]-shogaol, and zingerone, as evidenced by the findings in the systemic circulation. The study further highlights the importance of considering this interconversion and tissue distribution when determining the administration dosage of ginger constituent combinations for therapeutic benefits and clinical applications.